Uma análise da relação entre as compras por impulso, o endividamento pessoal e o nível de estresse financeiro - Oliveira, Carolina Helena Medeiros Alves de (Universidade Federal Rural do Semi-Árido, 2019)
Negative drinking habits affect people emotionally and / or financially. Thus, there is a need to address topics such as financial stress, impulse purchases and personal debt. Given this, the main objective of the present study was to analyze the influence of impulse purchases and indebtedness on the financial stress level of UFERSA Business Administration students. In addition to this objective, the present study also has as its specific objectives: to measure the level of financial stress of business students; analyze the relationship between impulse purchases and the level of financial stress; and analyze the relationship between debt and the level of financial stress. For this, a quantitative study of the explanatory type, with cross-sectional temporal cut was performed. The show consisted of 158 students and the collection was held in the classrooms of the university itself. The level of financial stress was measured from the InCharge Financial Stress / Financial Welfare Scale, developed by Prawitz et al. (2006) and the relationships between the constructs were analyzed by multiple linear regression and discriminant analysis. The results show that students have a high level of financial stress, that impulse purchases negatively affect the level of financial stress and that indebtedness positively affects the level of financial stress.
Monografia
Keywords: Nível de estresse financeiro; Compras; Endividamento; Financial stress level; Impulse shopping; Indebtedness; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO